2012
DOI: 10.1155/2012/818230
|View full text |Cite
|
Sign up to set email alerts
|

Antirheumatoid Arthritis Activities and Chemical Compositions of Phenolic Compounds-Rich Fraction fromUrtica atrichocaulis, an Endemic Plant to China

Abstract: Urtica atrichocaulis, an endemic plant to China, is commonly used to treat rheumatoid arthritis even though its pharmaceutical activities and chemical constituents were not studied. Herein, we reported our investigations on the chemical compositions of the phenolic compounds-rich fraction from U. atrichocaulis (TFUA) and their antirheumatoid arthritis activities. We found that the TFUA significantly inhibited the adjuvant-induced rats arthritis, carrageenin-induced rats paw edema, cotton pellet-induced mice gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…21 Some phenolics and flavonoids were reported to have a therapeutic effect on RA. 22 Thus the observed anti-arthritic activity of AMME is very likely due to the combined action of phenolic (quinic acids, inositol esters) and flavonoid (pyranone) compounds, which were found to be the major constituents by our GC/MS analysis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…21 Some phenolics and flavonoids were reported to have a therapeutic effect on RA. 22 Thus the observed anti-arthritic activity of AMME is very likely due to the combined action of phenolic (quinic acids, inositol esters) and flavonoid (pyranone) compounds, which were found to be the major constituents by our GC/MS analysis.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have suggested a strong relationship between antioxidant activity of plant extracts and their phenolic content, probably due to their redox properties, which allows them to act as reducing agents, hydrogen donors and singlet oxygen quenchers . Some phenolics and flavonoids were reported to have a therapeutic effect on RA . Thus the observed anti‐arthritic activity of AMME is very likely due to the combined action of phenolic (quinic acids, inositol esters) and flavonoid (pyranone) compounds, which were found to be the major constituents by our GC/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the side-effects of these anti-RA drugs, the fact that these drugs do not support a permanent cure, as well as the high cost of these medications make them unsatisfying for patients with RA. Natural medicines, belonging to the class of DMARDs, are characterized by their action on multiple targets of the disease pathway, low toxicity, and tunability, and hence play an essential role in the treatment of RA [15][16] . Among these natural drugs are the tripterygium glycosides (TG), with the main active ingredient being triptolide.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been an increasing number of reports that traditional Chinese medicines (TCMs) can serve as source of new, alternative drugs [7,8]. In addition, most RA patients are very likely to use plant-derived agents for treating RA [9,10]. These reports suggest that finding new RA drugs from commonly used TCMs may be a promising strategy.…”
Section: Introductionmentioning
confidence: 99%